Analysis of Ability to Solve Geometry Problems in terms of Spatial Ability of Class XII Students of SMA Cokroaminoto Tamalanrea Makassar - Setiawan Madya; Abdul Rahman; Ruslan Ruslan (PT ARRUS Intelektual Indonesia, 2023)
This study aims to describe the ability of class XII students of SMA Cokroaminoto Tamalanrea Makassar to solve geometry problems in terms of their spatial ability. This was a qualitative study with a descriptive approach. The selected subjects were three students in the 2022/2023 academic year. The selected subjects consisted of one from the high category of spatial abilities, one from the medium category, and one from the low category. The instruments in this study consisted of the main instrument, namely the researcher, and supporting instruments, namely spatial ability tests, problem-solving ability tests, and interview guidelines. Checking the validity of the data using source triangulation. Based on the results of the data analysis, it was concluded that: (1) students' mathematical problem-solving abilities in geometric materials with high spatial abilities were able to solve problems with four stages of problem-solving ability indicators: understanding the problem, preparing a solution plan, carrying out the settlement plan, and re-checking the solution; (2) students' mathematical problem-solving abilities in geometric material with moderate spatial abilities were able to solve problems with three stages of problem-solving ability indicators: understanding the problem, developing a solution plan, and carrying out the settlement plan; (3) students' mathematical problem-solving abilities in geometric material with low spatial abilities were not able to solve problems with four stages of problem-solving ability indicators, namely understanding the problem, planning the problem, carrying out the problem-solving plan, and re-checking the solution.